Antioxidant activity of aqueous extracts from Crataegus oxyacantha leaves - Loubna, Amor; Rachid, Belhattab (Pharmacognosy Communications)
Background: Crataegus (Rosaceae) genus comprises more than 200 species worldwide but few species have been used medicinally. In the Mediterranean region, the predominant species of this genus is C. oxyacantha syn. Monogyna (known as Hawthorn) which is protective against the treatment of mild heart diseases. Methods: The leaves were collected at three different stages (vegetative, flowering and fruiting). The aim of this work was to determine total phenol, flavonoid, flavon and flavonol contents, as well as antioxidant activity of hawthorn leaves aqueous extracts. Chemical determinations were carried out using spectrophotometric methods, whereas antioxidant activity was assessed according to 1,1 diphenyl-2-picrylhydrazyl( DPPH), iron chelating ability and reducing power. Results: Total phenol content varied from 96.75 to 168.92 mg gallic acid equivalent (GAE)/100 g of dry weight; flavonoids ranged from 3.9 ± 1.51 to 16.35 ± 2.51 mg of quercetin equivalent (QE)/100 g of dry weight from the extract of leaves at flowering, vegetative and fruiting stages respectively; and the flavons and flavonols ranged from 26.36 ± 1.02 to 40.16 ± 1.95 mg of quercetin equivalent (QE)/100 g of dry weight. The leaves extract at flowering stage showed high scavenging activity against the free radical DPPH with an IC50 value of 45.23 ± 0.07 µg/ml. The leaves extract from all the stages exhibited low ferrous chelating activity and reducing power activity (IC50 between 262.26 ± 1.32 and 506.04 ± 1.95 µg/ml) compared to BHA (IC50 41.41 ± 0.51 µg/ml).
Keywords: Antioxidant activity; C. oxyacantha; Hawthorn; Phenolic content; Rosaceae